1973
DOI: 10.1136/bjo.57.12.897
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins in aqueous humour and iris from patients with endogenous uveitis and patients with cataract.

Abstract: The scarcity of aqucous humour and uveal tissues from living patients has hampered studies on the immunological aspects of human eye diseases. There are many autopsy studies investigating the niature and amount of proteins in human aqueous, but it is known that the composition of aqueous humour changes very rapidly after death so that the validity of the results of these autopsy studies on the composition of aqueous humour is in doubt (Hemmingsen and Other, I967; Dieckhues, I967; Allansmith, Whitney, McClellan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1975
1975
1999
1999

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…This elevation of C3 was found to show some parallelism with the intraocular increase of IgA. In uveitis, albumin and IgG levels are definitely elevated, as Ghose et al [1973] have already shown. Their study however does not relate these protein levels to the degree of flare and cells.…”
Section: Resultssupporting
confidence: 54%
“…This elevation of C3 was found to show some parallelism with the intraocular increase of IgA. In uveitis, albumin and IgG levels are definitely elevated, as Ghose et al [1973] have already shown. Their study however does not relate these protein levels to the degree of flare and cells.…”
Section: Resultssupporting
confidence: 54%
“…Note that the appearance of IgG in the AH at 45 min post injection [ Fig. 1(C)] coincided with the paracellular permeability increase and is characteristic of uveitis (Ghose et al, 1973). Thus, we have elicited an uveitis-like condition in which the characteristic feature develops within a 15 min window (30-45 min) providing a unique opportunity for viewing underlying cellular mechanism.…”
Section: Discussionmentioning
confidence: 90%
“…Further, IgG (58 kD Fc fragment) was not detected in the control AH [ Fig. 1(C)] but was detected in the AH collected at 45 and 60 min post MDP injection, which is characteristic of eyes with uveitis (Ghose et al, 1973).…”
Section: Intracameral Mdp Increases Ah Total Protein Concentrationmentioning
confidence: 97%
“…18 Immune complexes have been extensivel) investigated in the sera and aqueous humor in AU,IX and although the results of the presenl study failed to reveal increased levels of immunt complexes, we have previously reported, using a more extensive battery of immune-compler assays, that such complexes are increased in tho HLA-B27-negative subgroup.8 Despite the lack of direct histological evidence for immune. complex deposition in man there is strong circumstantial and experimental evidence'' that such complexes may play a pathogenic role in certain patients with this disease.…”
Section: Discussionmentioning
confidence: 96%